Research on Software Fault Distribution for Web Application - Wanjiang Han; Lixin Jiang; Sun Yi; Li Ye; Han Xiao; Weijian Li; Liu Chi (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
This paper studies multiple software faultdistribution model, then extends the ideas of software fault estimation based on the analysis of a large number of projectfault data.Itpresents the estimation model of software faultsdistribution for Web Application, which refers to the G-O model and Rayleigh model. Thispaper fits the faultprediction model and showsthe steps to determine the relevant parameters.Firstly, estimating the probability of finding a faultaccording to similar project data.Then estimating the total number offaults. Software fault estimation model has certain directive significance to the prediction and planning projects.Experiments show that the model has great potential to predictsoftware fault. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.5116